Strengthening the Application of Discipline Rules as a Real Effort for Discipline Building - Muttaqien, Ishak (AKADEMIK: Jurnal Mahasiswa Humanis, 2022)
Learning is a comprehensive educational activity, which teaches all aspects, from science to attitude. This is as a unit, which is designed to prepare students who are insightful, knowledgeable, charitable, and have character. One of the contents in learning activities is about inculcating discipline values. Discipline rules are a necessity, so they must get special attention in their implementation. Schools and all their instruments must be consistent in upholding disciplinary values, starting from socialization to the application of sanctions for violations. This research was conducted in order to dig up information about the school's efforts in implementing disciplinary rules to order school personnel, especially students, to form disciplined behavior in learning and living. To reveal this phenomenon, the research was conducted naturally, with qualitative methods. The research analysis uses descriptive techniques with disclosure of information through interviews and observations. The object of the research is a middle-level Islamic educational institution in Parung Bogor. The subjects of this research are principals, teachers, and students. In the results of the study obtained information, that the school has disciplinary rules, which normatively must be obeyed by all school members. However, in the group of students, violations of the rules are still often found. The results of the interview obtained information, many factors that trigger acts of violation, including personality, the influence of friends and the playing environment, as well as problems at home. The school seeks to take measurable actions, including by socializing the rules of discipline, coaching, guidance, and imposing sanctions.